Calcification of Axial Skeleton and Segmentation Muscular Regeneration of Gecko’s Tail (Gekko Gecko Linnaeus, 1758) - Syarifah, Azkiya Zahrotus; Luthfi, Muhammad Ja’far; Khatimah, Alfiatun Wa’is Khusnul; Rahmah, Aulya Nidaur (Proceeding International Conference on Science and Engineering, 2019)
Gecko is an animal that can carry out autotomy. Research on gecko tail autotomy has been carried out, but there are still few who research the axial skeleton that focuses on vertebrae caudales and segmentation muscular arranged, this is the background of this research. This research is expected to be data base further research and as a comparison between animals that can induce further autotomy. This study aims to determine the macrostructure and microstructure of axial axial gecko tail regenerates and determine the anatomical microstructure of muscular regeneration of gecko tail. The methods used were X-Ray, Alizarin Red S and Alcian Blue, Paraffin method with hematoxylin-eosin staining, and Mallory Triple Stain. The results showed that the color of the gecko tail regenerate was paler compared to the original tail. On observations using radiological rays and alizarin staining showed that the original tail wo uld look segmented and have a process. The original gecko tail is composed of bones, because it is red which shows perfectly calcified bone. While the gecko tail regenerate is composed of cartilage that is shaped like a long pipe glazed red because it has calcified. At the end of the tail there is also a blue color, this indicates that the gecko tail regenerate has not been completely calcified. Segmentation Muscular of the original gecko tail, when viewed longitudinally, indicates a segment that extends from one process to the skin and when viewed from the cross has only four muscle segments separated by the septum. While the gecko tail regenerate when viewed in a longitudinal manner there is no segment and when seen transversely there are 12 muscle segments seen. Muscles are composed of a collection of myotubes that form myotomes, each myotomes limited by myoseptum.